Idebenone increases chance of stabilization/recovery of visual acuity in OPA1‐dominant optic atrophy. Issue 4 (3rd April 2020) - Romagnoli, Martina; La Morgia, Chiara; Carbonelli, Michele; Di Vito, Lidia; Amore, Giulia; Zenesini, Corrado; Cascavilla, Maria Lucia; Barboni, Piero; Carelli, Valerio
Abstract: We previously documented that idebenone treatment in OPA1 ‐Dominant Optic Atrophy ( OPA1 ‐DOA) led to some degrees of visual improvement in seven patients. We here present the results of a cohort study, which investigated the effect of off‐label idebenone administration in a larger OPA1 ‐DOA group compared with untreated patients. Inclusion criteria were: OPA1 ‐DOA clinical and molecular diagnosis, baseline visual acuity (VA) greater than/equal to counting fingers and treatment duration greater than 7 months. We found a significant difference between the last visit and baseline VA in favor of stabilization/recovery in idebenone‐treated as compared to untreated patients. This effect was retained after controlling for confounders.